The importance of genetic counselling and testing in inherited eye diseases: A population-based retrospective study - Michal Kaminer Abargel; Michal Macarov; Karen Hendler; Claudia Yahalom (PLoS ONE, 2025)
Purpose Inherited eye diseases (IEDs) are among the main causes of visual impairment and blindness in children and young people worldwide. The objective of our study was to characterize the prevalence and distribution of the most common IEDs and causative genes in our population. Study design Retrospective study based on medical records of patients with IEDs who underwent genetic counselling through our multidisciplinary low vision center from 2018 to 2020. Methods Data retrieved from medical files included: year of consultation, age, gender, ethnicity, diagnosis, gene variants and mode of inheritance. Results 228 patients were included in our study. The most common diagnoses were inherited retinal diseases (IRDs) (41.2%) and albinism (32%). In 2018 and 2019 the number of patients reaching out for genetic counselling was between 50 and 60; this number doubled by 2020. The rate of pathogenic variant detection was 65.3%. The most common genes identified were TYR (29.2%), OCA2 (7.9%), ABCA4 (5.3%), TRPM1 (5.3%) and USH2A (4.4%). Conclusion Genetic counselling and testing became an essential part of caregiving for patients and families affected by these severe IEDs. The most common IEDs were IRDs in the Muslim population and albinism in the Jewish population. Pathogenic variants in the TYR gene were the most common in our cohort, OCA2 gene was the second in frequency, followed by ABCA4, TRPM1 and USH2A genes. We detected an increasing trend over the studied time in the number of patients reaching out for genetic counselling.